Dressmaking courses of selected vocational programs in Metro Manila - Opinaldo, Crisel Inosanto; Elumba, Ma. Patricia S. (2002.)
The study entitled "Dressmaking courses of selected vocational Programs in Metro Manila" is a descriptive case study. It aims to give a better understanding on how vocational programs are conducted, thus can identify where and how dressmakers in the local government industry learn and acquire their skills. The research examines schools which offer vocational garment courses, namely Mirriam College in Katipunan, Samson College Cubao branch, and the Marikina Institute of Science and Technology, the Technical University of the Philippines, and the technical Education and Skills Development Authority (TESDA) in Taguig. The former Philippine School of Arts and Trade were not included as main respondents, although some information and facts from the said school were used. Primary source was a crop up interview from teachers and students involved in vocational programs. The curriculum from each school gave the necessary facts regarding the course, objectives, outlines, duration, et al.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Dressmaking -- Philippines -- Metro Manila -- Vocational guidance